Entry and Killing of Tetrahymena thermophila by Bacterially Produced Shiga Toxin - Gino Stolfa; Gerald B. Koudelka (mBio, 2013)
ABSTRACT Phage-encoded Shiga toxin (Stx) acts as a bacterial defense against the eukaryotic predator Tetrahymena thermophila. It is unknown how Stx enters Tetrahymena protozoa or how it kills them. Tetrahymena protozoa are phagocytotic; hence, Stx could gain entry to the cytoplasm through the oral apparatus or via endocytosis. We find that Stx2 can kill T. thermophila protozoa that lack an oral apparatus, indicating that Stx2 can enter these cells via endocytosis. As opposed to the lack of effect on mammalian phagocytes, Stx2 produced by bacteria encapsulated within phagocytotic vesicles is also capable of killing Tetrahymena. Addition of an excess of the carbohydrate binding subunits of Stx2 (StxB) and/or ricin (ricin B) blocks Stx2 cytotoxicity. Thus, regardless of whether Stx2 enters the cytoplasm by endocytosis or from the phagocytotic vesicle, this transport is mediated by a putative glycoconjugate receptor. Bacteriophage-mediated lysis of Stx-encoding bacteria is necessary for Stx toxicity in Tetrahymena; i.e., toxin released as a consequence of digestion of bacteria by Tetrahymena is harmless to the cell. This finding provides a rationale as to why the genes encoding Stx are found almost exclusively on bacteriophages; Stx must be released from the bacteria prior to the digestion of the cell, or it will not be able to exert its cytotoxic effect. It also suggests a reason why other bacterial exotoxins are also found only on temperate bacteriophages. Incubation of Tetrahymena with purified Stx2 decreases total protein synthesis. This finding indicates that, similar to mammalian cells, Stx2 kills Tetrahymena by inactivating its ribosomes. IMPORTANCE Tetrahymena is a bacterial predator and a model for mammalian phagocytosis and intracellular vesicular trafficking. Phage-encoded exotoxins apparently have evolved for the purpose of bacterial antipredator defense. These exotoxins kill mammalian cells by inactivating universally conserved factors and/or pathways. Tetrahymena and susceptible mammalian cells are killed when exposed to bacteriophage-encoded Shiga toxin (Stx). Stx toxicity in mammalian cells requires Stx binding to the globotriaosyl ceramide (Gb3) receptor, followed by receptor-mediated endocytosis (RME). We show that, similar to mammalian cells, internalized Stx inhibits protein synthesis in Tetrahymena. Although Tetrahymena lacks Gb3, our results suggest that the cytotoxic effect of Stx on Tetrahymena is apparently mediated by a receptor, thereby arguing for the existence of RME in Tetrahymena. As opposed to the case with mammalian phagocytes, Stx produced by bacteria inside Tetrahymena is cytotoxic, suggesting that these cells may represent a “missing link” between unicellular eukaryotic bacterial predators and phagocytotic mammalian cells.